Menyelisik Strategi Pengelola LPD Desa Adat Pedawa dalam Menekan Non Performing Loan (NPL) - Wahyuni, Luh Putu Novita; Dewi, Ni Wayan Yulianita (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This research was conducted to explore the management strategy of LPD in Pedawa Customary Village in suppressing NPLs. The research method applied in this research was descriptive qualitative method. Data were obtained through in-depth interviews, observation and study of documents which were then analyzed byanalysis interactive model from Milesand Huberman (1967). The results show that the occurrence of NPL problems in LPD decreases after the implementation of nunda tetegenan sanctions as an ancient tradition in Pedawa Customary Village. Nunda tetegenan consists of 3 levels, namely social sanctions, customary sanctions and witness sanctions. This nunda tetegenan sanction does not prohibit village manners from carrying out their obligations as religious people to carry out their yad activities, but rather delaying the right manners to acquire customary witnesses, postponing negen kena-kenaan banten piodalan but still being able to offer other offerings, and delaying the right to obtain services from Customary Villages.